Replacement of an aortic valve cusp after neonatal endocarditis. - Tulloh, R M (1990)
Septic arthritis developed in a neonate after an infection of her hand. Despite medical and surgical treatment endocarditis of her aortic valve developed and the resultant regurgitation required emergency surgery. At operation a new valve cusp was fashioned from preserved calf pericardium. Nine years later she was well and had full exercise tolerance with minimal aortic regurgitation.